Theory of Mind and Cognitive Function in Adults with Alström or Usher Syndrome. (September 2016) - Henricson, Cecilia; Frölander, Hans-Erik; Möller, Claes; Lyxell, Björn
Objective: Theory of mind (ToM) refers to the ability to impute mental states to one's self and others. ToM was investigated in adults with Usher syndrome type 2 (USH2) or Alström syndrome (AS). Both syndromes cause deafblindness, but differ with regard to onset and degree of sensory loss. Individuals with AS, furthermore, display additional physical diseases. Comparisons were made with individuals with typical hearing and vision. Methods: Thirteen people with USH2, 12 people with AS, and 33 people with typical hearing and vision performed tests of working memory capacity and verbal ability. ToM was tested via Happé's Strange Stories, assessing ability to understand the emotions and actions of story characters. The test also included matched physical stories to evaluate understanding of the logical outcomes associated with everyday situations. Results: Significant differences were identified in problem solving regarding physical conditions, with higher scores for the typical hearing and vision group, H (2) = 22.91, p < 0.01. The two groups with deafblindness also demonstrated poorer ToM than the typical hearing and vision group, H (2) = 21.61, p < 0.01, and the USH2 group outperformed the AS group, U (34), z = 2.42, p = 0.016. Intra-group variability was related to working memory capacity, verbal ability, visual status, and to a minor extent auditory capacity. The prevalence of the additional physical diseases was not related to ToM performance. Conclusions: Limited access to information due to visual loss may have reduced the degree of social experience, thereby negatively affecting the development of ToM. That working memory capacity and verbal ability displayed an impact implies that hearing also contributes to ToM development. Differences between the two groups might be a function of genetic conditions, in which the gene causing USH2 only affects the ears and the eyes, whereas AS has a multisystemic pathology. Implications for practitioners: Advice and support technology should emphasize ease of communication and boost the development of the communication required to develop ToM.